2023
DOI: 10.3390/molecules28104096
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thymoquinone-Sulfobutylether-β-Cyclodextrin Inclusion Complex for Anticancer Applications

Abstract: Thymoquinone (TQ) is a quinone derived from the black seed Nigella sativa and has been extensively studied in pharmaceutical and nutraceutical research due to its therapeutic potential and pharmacological properties. Although the chemopreventive and potential anticancer effects of TQ have been reported, its limited solubility and poor delivery remain the major limitations. In this study, we aimed to characterize the inclusion complexes of TQ with Sulfobutylether-β-cyclodextrin (SBE-β-CD) at four different temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The phase solubility diagram was found to be of three types based on solubility: A L type (increase in CD concentration led to drug enhancement), A P type (CD more effective at high concentrations), and A N type (negatively deviated straight line due to CD is more effective at low concentrations). In this study, the graph was found to be of A L type . For both the binary and ternary systems, the slopes of the phase solubility curves were smaller than unity.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The phase solubility diagram was found to be of three types based on solubility: A L type (increase in CD concentration led to drug enhancement), A P type (CD more effective at high concentrations), and A N type (negatively deviated straight line due to CD is more effective at low concentrations). In this study, the graph was found to be of A L type . For both the binary and ternary systems, the slopes of the phase solubility curves were smaller than unity.…”
Section: Resultsmentioning
confidence: 56%
“…In this study, the graph was found to be of A L type. 39 For both the binary and ternary systems, the slopes of the phase solubility curves were smaller than unity. It was hypothesized that the drug and CD would form 1:1 M stoichiometric inclusion complexes in solution.…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, SBE-β-CD has been successfully investigated for controlled drug release and antibacterial efficacy using nanofibers and nanoparticles techniques [17]. Previously, we investigated the formation of inclusion complexes between TQ and SBE-β-CD to improve the solubility and delivery of TQ, and the results demonstrated that the inclusion complexes significantly enhanced TQ's solubility and exhibited improved anticancer effects, suggesting the potential of SBE-β-CD as a drug delivery system for TQ, though further research is needed [13]. Anticancer therapy focuses on targeting telomeres and telomerase, as they play crucial roles in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing a nanoformulation approach such as SBE-β-CD, the effectiveness of TQ can be significantly enhanced. Thus, TQ/SBE-β-CD holds great promise as a potential strategy for cancer treatment [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation